2019
DOI: 10.1186/s13007-019-0545-2
|View full text |Cite
|
Sign up to set email alerts
|

PI-Plat: a high-resolution image-based 3D reconstruction method to estimate growth dynamics of rice inflorescence traits

Abstract: BackgroundRecent advances in image-based plant phenotyping have improved our capability to study vegetative stage growth dynamics. However, more complex agronomic traits such as inflorescence architecture (IA), which predominantly contributes to grain crop yield are more challenging to quantify and hence are relatively less explored. Previous efforts to estimate inflorescence-related traits using image-based phenotyping have been limited to destructive end-point measurements. Development of non-destructive inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
1
25
0
1
Order By: Relevance
“…The morphometric parameters of inflorescence are highly correlated with yield and grain quality (Leilah and Al-Khateeb, 2005;Gegas et al, 2010). Several studies discussed about using image-based techniques (2D images/3D reconstruction) to extract architectural traits such as length and width of inflorescence, inflorescence volume (weight), grain shape and size, grain angle, and number of grains, and number of flowers (Faroq et al, 2013;Crowell et al, 2014;Gage et al, 2017;Rudolph et al, 2019;Sandhu et al, 2019;Xiong et al, 2019;Zhou et al, 2019). In such applications to measure the morphological traits, a robot with LIDAR/camera can be useful to automatically take images/point cloud data from different views of the inflorescence.…”
Section: Perspective Applications Of Robotic Phenotypingmentioning
confidence: 99%
“…The morphometric parameters of inflorescence are highly correlated with yield and grain quality (Leilah and Al-Khateeb, 2005;Gegas et al, 2010). Several studies discussed about using image-based techniques (2D images/3D reconstruction) to extract architectural traits such as length and width of inflorescence, inflorescence volume (weight), grain shape and size, grain angle, and number of grains, and number of flowers (Faroq et al, 2013;Crowell et al, 2014;Gage et al, 2017;Rudolph et al, 2019;Sandhu et al, 2019;Xiong et al, 2019;Zhou et al, 2019). In such applications to measure the morphological traits, a robot with LIDAR/camera can be useful to automatically take images/point cloud data from different views of the inflorescence.…”
Section: Perspective Applications Of Robotic Phenotypingmentioning
confidence: 99%
“…Research into using remote sensing to quantify seed number and grain weight of a plant in a field environment is limited. There has been success in controlled environments in which a 3D reconstruction of rice showed that seed number for the panicle had a significant ( P <0.05) positive correlation with the voxel count of the reconstruction throughout the grain-filling period ( r =0.61–0.70) ( Sandhu et al , 2019 ). This same experiment also found a significant ( P <0.05) positive correlation ( r =0.48–0.74) between voxel count and seed weight which increased approaching maturity.…”
Section: Estimating Yield and Key Yield-related Parametersmentioning
confidence: 99%
“…Plants were grown in a glasshouse under controlled conditions (16 h 30 AE 1°C : 8 h 23 AE 1°C, light : dark, relative humidity 55-60%). At 1 d after c. 50-70% of the primary panicle underwent flowering (Sandhu et al, 2019), three plants from each accession were transferred to a glasshouse under 16 h 30 AE 1°C : 8 h 28 AE 1°C, light : dark conditions for a terminal HNT treatment and the remaining three plants for each accession were maintained under the control glasshouse conditions (30 AE 1°C : 23 AE 1°C, light : dark). HNT stress and control conditions for this study represent the glasshouse air temperatures.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%